"Le tega je uržoh Jožef cesar ta, Bog dej, de bi biu skorej en drugi..." - Golec, Boris (Zgodovina za vse, 2000)
The article presents six poetic texts, written in the Slovene language in the period from the death of Maria Teresa (1780) to the first fall of Napoleon (1814). The texts, all of which are anonymous versifications, are very different in style and quality, and cover quite a wide range of themes - from a panegyric on the ruler to a severe criticsm of the society of the times, the policies implemented by the emporer, and even his personality. The poems were written by the "conservative" part of the clergy and perhaps in part also by members of the laity. Due to their predominantly "improper" content, four of them were never published and were disseminated only in handwritten form. Up until now, only two of these poems were published, one of these two being a pamphlet against Enlightenment and Janseism. In it, the Slovene word for "enlightened" is mentioned for the first time.
Keywords: 18.st.; poezija; slovenska književnost